Responses of peatland vegetation to 15-year water level drawdown as mediated by fertility level - Nicola A K Kokkonen; Anna Maria Laine; Jukka Laine; Harri Vasander; Kirsi Kurki; Jinnan Gong; Eeva-Stiina Tuittila (PANGAEA, 2019)
Peatland vegetation community data following experimental water level manipulation with measurements repeated six times in 15 years.
Supplement to: Kokkonen, NAK et al. (2019): Responses of peatland vegetation to 15-year water level drawdown as mediated by fertility level. Journal of Vegetation Science, 30(6), 1206-1216, https://doi.org/10.1111/jvs.12794